2014
DOI: 10.1007/s40279-014-0190-x
|View full text |Cite
|
Sign up to set email alerts
|

Applied Sport Science of Rugby League

Abstract: Rugby league is a team sport in which players engage in repeated high-intensity exercise involving frequent collisions. Recent research, much of which has involved global positioning system (GPS) technology, has provided coaches and sport scientists with a deeper understanding of match demands, particularly at the elite level. This has allowed for the development of training programmes that prepare players for the most intense contact and running demands likely to be experienced in competition. At the elite le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
215
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(222 citation statements)
references
References 108 publications
4
215
0
3
Order By: Relevance
“…Regardless of sex, the greater body mass and stature of forwards are likely favourable for their respective positional requirements, as forwards are involved in more collisions than backs (21). The stature and body mass of players from this respective English cohort were shorter and heavier than their Australian counterparts (forwards and backs; 169.0 ± 6.6 and 166.1 ± 65.4 cm, and 75.5 ± 12.5 and 64.7 ± 7.6 kg (14)).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regardless of sex, the greater body mass and stature of forwards are likely favourable for their respective positional requirements, as forwards are involved in more collisions than backs (21). The stature and body mass of players from this respective English cohort were shorter and heavier than their Australian counterparts (forwards and backs; 169.0 ± 6.6 and 166.1 ± 65.4 cm, and 75.5 ± 12.5 and 64.7 ± 7.6 kg (14)).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in male rugby league players have shown that forwards are involved in more collisions, while backs are involved in more high-speed (>5 m.sec -1 ) running (39, 40). Previous studies in males (10)(11)(12)(13)21) have identified forwards are taller, heavier, stronger and more powerful, with higher body fat than backs. Backs are reportedly faster, more agile, with a greater aerobic capacity than forwards (21).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations